Case Studies on Acupuncture Principles in Headaches - Saroj Kumar Pradhan (Chinese Medicine and Culture, 2021)
Objective: This observational cohort pilot study aimed to evaluate the effects of the acupuncture methods, Jiu Cang Zhen (JCZ) and Huang Guan (HG), on changes in headache intensity in an inpatient, multimodal Zurzach Headache Programme (ZHP). Methods: Study participants consisted of patients diagnosed with chronic headache disorder (headache ds, 30 days per month) or daily persistent headache. All patients received conventional therapies with active and passive approaches. The patient group was treated with JCZ and HG acupuncture methods, receiving a total of six to eight acupuncture sessions of 50 to 60 minutes each, during a 3–4-week multimodal ZHP at the RehaClinic Bad Zurzach. Pain intensity was quantified using a Numerical Rating Scale (NRS) before and after each acupuncture therapy session. Results: Ten patients were recruited, six women and four men, with a mean age of 41.7 (standard deviation, [SD] =13.9). A reduction in headache intensity was reported by all patients in each of the sessions. The average NRS for pain was 4.21 (SD = 1.44) before acupuncture and 1.24 (SD = 0.93) after acupuncture (means first by number of sessions, then per n = 10 patients). This resulted in a mean difference of 2.97 (SD = 1.04), corresponding to a standardized response mean of 2.85 (95% confidence interval: 2.11–3.60, one-tailed P < 0.001), meaning there was a large effect. Conclusions: This pilot study shows that JCZ and HG are suitable acupuncture methods for reducing headache intensity in the treatment of headaches. A comparison with the conventional classical acupuncture methods from the acupuncture textbook for traditional Chinese medicine students in China, exploration with a larger patient group, and prolonged monitoring of pain behavior could be foci of follow-up investigations.